Mechanosensitive phosphorylation of NFATC4 at S213/S217 drives fibroblast-to-myofibroblast transition and fibrosis - Safwen Kadri; Laura F. Mattner; Zhen Zeng; Sai Rama Sridatta Prakki; Arun Kumar Verma; Umut Cetin; Christoph H. Mayr; Meshal Ansari; Xin Wei; Sara Asgharpour; Anita A. Wasik; Nikolaus Kneidinger; et al. (Journal of Clinical Investigation, 2026)
Mechanosensitive feedback between tissue stiffness and cellular contractile forces instructs cell identity. To characterize phosphorylation-mediated mechanosensing, we charted the global phosphoproteome dynamics of primary human lung fibroblasts on fibronectin-coated polydimethylsiloxane substrates of defined stiffness. We identified a key signaling threshold at 2–8 kPa, above which cells activated cytoskeletal remodeling, ECM secretion, and transition to a CTHRC1 + / ACTA2 + myofibroblast state, accompanied by stiffness-dependent phosphorylation of the transcription factor NFATC4 at S213/S217. In micro-CT staged pulmonary fibrosis tissues, NFATC4 expression increased progressively, colocalizing with CTHRC1 and ACTA2 in myofibroblasts. Transcription factor regulon inference from a multicohort pulmonary fibrosis atlas confirmed elevated NFATC4 activity in disease fibroblasts, revealing a core 119-gene NFATC4 -dependent fibrotic program with CTHRC1 as a top target. Phosphomimetic S213D/S217D mutants drove myofibroblast differentiation on soft substrates independently of TGFB , while phospho-dead S213A/S217A mutants blocked differentiation even on stiff matrix with TGFB , establishing the phospho-switch as both necessary and sufficient. Stiff matrix and TGFB converged on this JNK - and calcineurin-dependent switch to amplify the fibrotic response. This positions NFATC4 S213/S217 as a mechanosensitive checkpoint for CTHRC1 + myofibroblast fate and a candidate therapeutic target in multiorgan fibrosis.